Efektivitas Multimedia Gamifikasi dalam Pembelajaran Berpikir Komputasional di SMP: Systematic Literature Review - Yuventus Monemnasi; Ketut Agustini; I Kadek Suartama (Cetta: Jurnal Ilmu Pendidikan, 2026)
The implementation of the Merdeka Curriculum emphasizes the strengthening of Computational Thinking (CT) skills as an essential competency in informatics learning at the junior high school level. However, CT instruction in junior high schools still faces several challenges, including low student motivation and engagement, limited availability of interactive learning media, and varying levels of teacher readiness in integrating technology. This study aims to analyze the effectiveness of gamification-based multimedia in improving junior high school students’ CT skills, identify supporting and inhibiting factors in its implementation, and map research gaps in studies published between 2021 and 2025. The research employed a Systematic Literature Review (SLR) method following the PRISMA protocol. Literature searches were conducted through Google Scholar, ERIC, and Scopus databases, resulting in 21 scientific articles that met the inclusion criteria. Data were analyzed using thematic synthesis to examine gamification strategies and their impacts on CT indicators, namely algorithmic thinking, decomposition, pattern recognition, and abstraction. The findings indicate that gamification strategies such as point–level–badge systems, progressive challenges, interactive simulations, and digital puzzles are consistently effective in enhancing algorithmic thinking, decomposition, and pattern recognition. In contrast, improvement in the abstraction component remains relatively limited and requires additional reflective and concept-oriented instructional approaches. The success of gamification implementation is influenced by interactive media design, instant feedback, and increased student motivation, while major challenges include limited ICT infrastructure and teachers’ digital competence. The novelty of this article lies in its cross-study synthesis of empirical research from 2021 to 2025, which systematically maps the dominant patterns of CT improvement within the context of junior high school education and the implementation of the Merdeka Curriculum. These findings provide both conceptual and practical contributions to the development of more effective and sustainable informatics learning.